Evaluation of electrosynthesized reduced graphene oxide–Ni/Fe/Co-based (oxy)hydroxide catalysts towards the oxygen evolution reaction - Cysewska, Karolina; Łapiński, Marcin; Zając, Marcin; Karczewski, Jakub; Jasiński, Piotr; Molin, Sebastian (Beilstein Journal of Nanotechnology, 2023)
In this work, the specific role of the addition of graphene oxide (GO) to state-of-the-art nickel–iron (NiFe) and cobalt–nickel–iron (CoNiFe) mixed oxides/hydroxides towards the oxygen evolution reaction (OER) is investigated. Morphology, structure, and OER catalytic activity of the catalysts with and without GO were studied. The catalysts were fabricated via a two-step electrodeposition. The first step included the deposition of GO flakes, which, in the second step, were reduced during the simultaneous deposition of NiFe or CoNiFe. As a result, NiFe-GO and CoNiFe-GO were fabricated without any additives directly on the nickel foam substrate. A significant improvement of the OER activity was observed after combining NiFe with GO (OER overpotential η(10 mA·cm−2): 210 mV) compared to NiFe (η: 235 mV) and GO (η: 320 mV) alone. A different OER activity was observed for CoNiFe-GO. Here, the overall catalytic activity (η: 230 mV) increased compared to GO alone. However, it was reduced in comparison to CoNiFe (η: 224 mV). The latter was associated with the change in the morphology and structure of the catalysts. Further OER studies showed that each of the catalysts specifically influenced the process. The improvement in the OER by NiFe-GO results mainly from the structure of NiFe and the electroactive surface area of GO.
Keywords: electrocatalysts; electrodeposition; energy; hydrogen; oxygen evolution reaction